التجارة الإلكترونية في ليبيا الواقع وأفاق المستقبل (Comprehensive Journal of Science, 2026)
This study aimed to highlight the digital transformation that has become a defining feature of our time, and to demonstrate its role in the development of e-commerce, which receives significant attention from countries. E-commerce relies on modern technology to produce goods and services quickly. The central question of this study is:What is the reality of the spread and use of e-commerce in Libya during 2024/2025, and what are the characteristics of its users in terms of usage level, nature of business activity, and purchasing behavior patterns? This question will be answered within this research. The study is significant as it contributes to enriching scientific knowledge related to e-commerce within the Libyan context, considering it a modern phenomenon involving intertwined cultural, organizational, and technological aspects. By analyzing the reality of usage during 2024/2025, the study provides a knowledge framework that helps understand the nature of Libyan consumers' adoption of digital purchasing behavior, based on interconnected social, technological, and economic variables. This study concludes with a number of findings, including that e-commerce has become one of the most important sectors that most countries worldwide strive to utilize due to its ease, unlike traditional commerce systems which require time. E-commerce saves time. The researcher recommends further academic studies related to examining e-commerce and highlighting its benefits, advantages, and disadvantages on the economic conditions of countries.
Keywords: E-commerce - Economy - Social conditions - State - Digital transformation - Modern technology